RANCANG BANGUN ALAT PENGERING KERUPUK RAMBAK IKAN LAUT DI KUBE SARI ENAK WOTGALEH SUKOHARJO - Darsini Darsini; Suprapto Suprapto; Budi Wibowo (Politeknik Negeri Ketapang, 2023)
The Sukoharjo sub-district is one of the sub-districts in the city center, but the income of the population who are farm laborers reaches 1,485 people, and the others reach 1,883 people. In this village there are also 44 small industries engaged in the production of snacks. One of these small industries has formed a joint business group called KUBE